Oven-Baked Architecture & Embodied Earth, Re-purposing a decommissioned quarry in Paarl, with a focus on the interface between people, architecture and the Earth - Trouw, Neil (School of Architecture, Planning and Geomatics, 2023)
This dissertation is about architecture. However this dissertation is about what architecture isn't as well. It is an intersectional investigation into the boundaries of architecture and where they lie. This is understood in the context of people, architecture and the Earth. Where exactly does mankind start and end and when do we become nature. How does architecture form the threshold between these conditions. A brick quarry in Paarl forms the site of this investigation. In a place characterized by a confrontation between people and the ground. A scar in the landscape, that begs to be addressed. Through the application of theoretic principles in the design process, a mediating architecture is uncovered.